Use of Screening Tests, Diagnosis Wait Times, and Wait-Related Satisfaction in Breast and Prostate Cancer - M. Mathews; D. Ryan; V. Gadag; R. West (Current Oncology, 2014)
Background: Understanding factors relating to the perception of wait time by patients is key to improving the patient experience. Methods: We surveyed 122 breast and 90 prostate cancer patients presenting at clinics or listed on the cancer registry in Newfoundland and Labrador and reviewed their charts. We compared the wait time (first visit to diagnosis) and the wait-related satisfaction for breast and prostate cancer patients who received regular screening tests and whose cancer was screening test–detected (“screen/screen”); who received regular screening tests and whose cancer was symptomatic (“screen/symptomatic”); who did not receive regular screening tests and whose cancer was screen test–detected (“no screen/screen”); and who did not receive regular screening tests and whose cancer was symptomatic (“no screen/symptomatic”). Results: Although there were no group differences with respect to having a long wait (greater than the median of 47.5 days) for breast cancer patients (47.8% screen/ screen, 54.7% screen/symptomatic, 50.0% no screen/ screen, 40.0% no screen/symptomatic; p = 0.814), a smaller proportion of the screen/symptomatic patients were satisfied with their wait (72.5% screen/ screen, 56.4% screen/symptomatic, 100% no screen/ screen, 90.9% no screen/symptomatic; p = 0.048). A larger proportion of screen/symptomatic prostate cancer patients had long waits (>104.5 days: 41.3% screen/screen, 92.0% screen/symptomatic, 46.0% no screen/screen, 40.0% no screen/symptomatic; p = 0.011) and a smaller proportion of screen/ symptomatic patients were satisfied with their wait (71.2% screen/screen, 30.8% screen/symptomatic, 76.9% no screen/screen, 90.9% no screen/symptomatic; p = 0.008).